2005
DOI: 10.1016/j.amjhyper.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Does Aldosterone-to-Renin Ratio Predict the Antihypertensive Effect of the Aldosterone Antagonist Spironolactone?

Abstract: Background:The recognition that some 10% to 15% of the hypertensive population may have aldosterone excess has increased the frequency of measurement of the aldosterone-to-renin ratio (ARR) and the use of aldosterone antagonists. Whether this ratio will predict the blood pressure (BP) response to spironolactone is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 14 publications
3
40
1
2
Order By: Relevance
“…Mamhud et al (39) evaluated the BP response to adding 50 mg of spironolactone to patients whose BP was uncontrolled on three agents. At 14 wk of follow-up, the mean BP reduction was 28 Ϯ 3/13 Ϯ 2 mmHg.…”
Section: Aldosterone Antagonists and Treatment Of Resistant Hypertensionmentioning
confidence: 99%
“…Mamhud et al (39) evaluated the BP response to adding 50 mg of spironolactone to patients whose BP was uncontrolled on three agents. At 14 wk of follow-up, the mean BP reduction was 28 Ϯ 3/13 Ϯ 2 mmHg.…”
Section: Aldosterone Antagonists and Treatment Of Resistant Hypertensionmentioning
confidence: 99%
“…4 Goodfriend also alludes to the fact that there was no pretreatment measurement of aldosterone or renin. In our study 3 for individuals commencing spironolactone as a first line antihypertensive therapy, age and pretreatment renin and ARR were good predictors of BP reduction. However, in the setting of individuals with resistant hypertension on multiple agents, neither renin nor ARR was a predictor of the hypotensive response.…”
Section: Spironolactone In Resistant Hypertensionmentioning
confidence: 87%
“…Although there are some data to suggest that a high ARR, a suppressed PRA, 24 and/or a low serum potassium level 19,25 predict a favorable response to aldosterone blockade, such predictive value has not been definitively established in blinded studies that included active comparators, and in fact, was specifically absent in the multicenter studies leading to approval of eplerenone, at least in patients already receiving an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker. 26 Accordingly, it is premature to recommend using the ARR to guide preferential use of mineralocorticoid receptor antagonists.…”
Section: Screening For Pamentioning
confidence: 99%
“…The value is not in initiating therapy with a mineralocorticoid receptor antagonist, because, interestingly, we and others have found that the blood pressure response to aldosterone blockade in patients being treating for resistant hypertension is not predicted by the ARR, PRA, or by urinary or plasma aldosterone levels. 18,24 This lack of predictive value is likely in part a consequence of confounding effects of ongoing treatment but also suggests a role of aldosterone in contributing to treatment resistance that is not reflected in the measurement of circulating levels.…”
Section: Screening For Pamentioning
confidence: 99%